2003
DOI: 10.1021/ic0207045
|View full text |Cite
|
Sign up to set email alerts
|

Photothermally Induced Bergman Cyclization of Metalloenediynes via Near-Infrared Ligand-to-Metal Charge-Transfer Excitation

Abstract: Reaction of 1,2-bis(tert-butyldimethylsilyloxy)-4,5-diiodobenzene with 2 equiv of phenylacetylene followed by deprotection with KF/HBr yields the catechol-enediyne ligand 4,5-bis(phenylethynyl)benzene-1,2-diol (CatED, 1). Metathesis of VO(SALIMH)ACAC.CH(3)OH (2) with 1 and subsequent air oxidation yields (4,5-bis(phenylethynyl)-1,2-dihydroxyphenyl)[4-(2-(salicylideneamino)ethyl)imidazolyl]oxovanadium(V).CH(3)OH [VO(SALIMH)CatED], (3), in 85%. The thermal Bergman cyclization temperature for 3 is very high (246 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…It has been shown that the cyclization reaction in enediynes is associated with an exothermic peak in DSC. 6,[22][23][24][25] Thermogravimetric analyses (TGA) (Supporting information Fig. S1) and DSC (Fig.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…It has been shown that the cyclization reaction in enediynes is associated with an exothermic peak in DSC. 6,[22][23][24][25] Thermogravimetric analyses (TGA) (Supporting information Fig. S1) and DSC (Fig.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…34). Bergman cyclization (576) of simple metalloenediynes have been reported (577,578). The first of these involves direct copper-pyridine charge-transfer photoexcitation (cf.…”
Section: Electronic Structure Contributions To Thermal Bergman Cyclizmentioning
confidence: 99%
“…In a slightly different approach to photochemical Bergman cyclization by CT excitation, the development of a long-wavelength, enediyne LMCT transition was used to thermally heat the metalloenediyne complex by nonradiative decay. The choice of V(V) coupled with a catechol-enediyne motif (Scheme 97) generates a strong LMCT transition (e $8000 M À1 cm À1 ) at 1032 nm that is used to photochemically (l ¼ 785 or 1064 nm) generate sufficient thermal energy to create Bergman and polymerized product (578). The photoreaction is monitored by Raman spectroscopy that shows luminescence from the photoproducts that builds during the timecourse of the photolysis.…”
Section: Electronic Structure Contributions To Thermal Bergman Cyclizmentioning
confidence: 99%
“…Besides thermal Bergman cyclization, Kraft et al elaborated a distinctive photo-initiated route. [11] Excitation of metalloenediynes in solid state with l ¼ 785 nm diode laser led to metallo-poly (p-phenylene) as a black material insoluble in many common solvents. The polymeric materials possessed M w ¼ 5 600 and M n ¼ 4 170 corresponding with an average of 9-10 monomeric units.…”
Section: Introductionmentioning
confidence: 99%